Zakat Calculation Model as a Reduction Factor for Income Tax Based on Law Number 11 of 2006 concerning the Government of Aceh (International Journal of Scientific Research and Management (IJSRM), 2024)
The purpose of this study is to examine the implementation of the provisions of Law Number 11 of 2006, especially Article 192 which regulates Zakat as a deduction from income tax. In this study, the researcher examines the extent to which this rule is applied in practice and attempts to evaluate the most effective zakat calculation model as a deduction from income tax. This study uses qualitative methods through interviews, observations, and documentation regarding Zakat as a deduction from tax. The research findings indicate that the implementation of the provision of zakat as a deduction from tax as regulated in Article 192 of Law Number 11 of 2006 has not been optimal in Aceh, especially in Lhokseumawe City. Although this law provides a strong legal basis, the practice in this field still refers to Law Number 23 of 2011 concerning Zakat Management. The implementation of Law Number 23 of 2011 in Lhokseumawe only focuses on the administration and distribution of zakat without providing clear guidelines in integrating zakat into the taxation system, thus inhibiting the use of zakat as a tax reduction tool.